Réponses

2013-05-05T16:59:31+02:00

A= (2x+1 )² = ²x 2x + ²x 1

 

B=(7x-1) (7x+1) +7 x (+1x-1) 

 

C=(x-4)²+(x+2)(x+3) = x²  X (4-2+3)

2013-05-05T17:04:04+02:00

Voici les répones que j'ai trouvé

a) (2x+1)²  [identité remarquable (a+b)²=a²+2ab+b²]

     2x²+4x+1

 

b) (7x-1)(7x+1) [identité remarquable (a+b)(a-b)=a²-b²]

     7x²-1

 

c) (x4)²-(x+2)(x+3)   [identité remarquable (a-b)²=a²-2ab+b²]

   =x²-8x+16-(x+2)(x+3) [ on dévellope ]

   =x²-8x+16-x²+3x+2x+6 [x*x=x² ; x*3=3x ; 2*x=2x ; 2*3=6]

   =-3x+22 [x²-x²=0 ; -8x+3x+2x=-3x ; 16+6=22]